COMPARISON OF ANAESTHETIC EFFICACY OF ARTICAINE AND LIDOCAINE IN NONSURGICAL ENDODONTIC TREATMENT OF PERMANENT MANDIBULAR MOLARS WITH SYMPTOMATIC IRREVERSIBLE PULPITIS. A RANDOMIZED CLINICAL TRIAL - Khan, Quratulain; Noor, Nouman; Anayat, Nouman; Khan, Tayyaba Sehrish; Ahmed, Manzoor (Journal of Ayub Medical College Abbottabad, 2021)
Background: Inferior Alveolar Nerve Block (IANB) with Buccal Infiltration (BI) anaesthesia is required to completely anesthetize the mandibular molars with symptomatic irreversible pulpitis. 4% Articaine and 2% Lidocaine provide local anaesthesia during the nonsurgical endodontic treatment of mandibular molars with symptomatic irreversible pulpitis. Objective of the study was to compare the effect of Articaine and Lidocaine in the combination of Inferior alveolar nerve block with buccal infiltration anaesthesia during the nonsurgical endodontic treatment of mandibular molars with symptomatic Irreversible Pulpitis. Method: One hundred and sixty participants with Symptomatic Irreversible Pulpitis of permanent mandibular molars were divided randomly in two groups. Group A was given Articaine 4% IANB along with BI whereas group B was given Lidocaine 2%. Pain was assessed after 15 minutes of administration of local anaesthesia. Anaesthetic success of the agents is defined as, absence of pain or mild pain first during the access cavity preparation then instrumentation of the canals of tooth. Chi-square test was applied to analyse data for statistical significance. Results: Anaesthetic success of Articaine was 96.2% during access cavity preparation compared to Lidocaine (86.2%). Success during instrumentation of canals was also found to be high in Articaine (90.2%) compared to Lidocaine (76.2%). This difference of anaesthetic efficacy between Articaine and Lidocaine was found statistically significant. (p=0.02) Conclusion: Articaine is found to be better than Lidocaine regarding anaesthetic efficacy and hence, it can be a safer alternative to Lidocaine.